This Service Terminates Here? Politics, Practitioner Perspectives, and the Future of Railway Policing in Scotland. (8th November 2018) - Murray, Kath; Atkinson, Colin
Abstract: Following the devolution of railway policing under the Scotland Act 2016, the Railway Policing (Scotland) Act 2017 set in motion a process that, if completed, will see the British Transport Police's Scottish Division integrated into Scotland's relatively new national police force, Police Scotland. The post-legislative journey has, however, proven far more challenging than supporters of integration envisaged. Drawing upon primary and secondary data, this article investigates the integration process to date and shows how a politicized and poorly managed transition programme left employees disillusioned, and fostered a deep strain of mistrust towards the project. With escalating costs, a lack of practitioner buy-in, the potential loss of experienced officers and staff, longer-term risks to the remaining BTP organization, and no clear evidence of benefits, the article concludes that the Scottish Government should call off full integration and consider an alternative approach towards the devolution of railway policing.